Biochemical evidence for conformational variants in the anti-viral and pro-metastatic protein IFITM1 - Nekulová, Marta; Wyszkowska, Marta; Friedlová, Nela; Uhrík, Lukáš; Zavadil Kokáš, Filip; Hrabal, Václav; Hernychová, Lenka; Vojtěšek, Bořivoj; Hupp, Ted R; Szymański, Michał R (Biological chemistry, 2024)
Interferon induced transmembrane proteins (IFITMs) play a dual role in the restriction of RNA viruses and in cancer progression, yet the mechanism of their action remains unknown. Currently, there is no data about the basic biochemical features or biophysical properties of the IFITM1 protein. In this work, we report on description and biochemical characterization of three conformational variants/oligomeric species of recombinant IFITM1 protein derived from an Escherichia coli expression system. The protein was extracted from the membrane fraction, affinity purified, and separated by size exclusion chromatography where two distinct oligomeric species were observed in addition to the expected monomer. These species remained stable upon re-chromatography and were designated as "dimer" and "oligomer" according to their estimated molecular weight. The dimer was found to be less stable compared to the oligomer using circular dichroism thermal denaturation and incubation with a reducing agent. A two-site ELISA and HDX mass spectrometry suggested the existence of structural motif within the N-terminal part of IFITM1 which might be significant in oligomer formation. Together, these data show the unusual propensity of recombinant IFITM1 to naturally assemble into very stable oligomeric species whose study might shed light on IFITM1 anti-viral and pro-oncogenic functions in cells.
Keywords: Antiviral Agents; IFITM proteins; Antigens, Differentiation; hydrogen deuterium exchange; oligomerization; Protein Conformation; protein structure; rekombinantní proteiny; Humans; lidé; Recombinant Proteins; antivirové látky; protein conformation; diferenciační antigeny; konformace proteinů